Endothelial tip cells in vitro are less glycolytic and have a more flexible response to metabolic stress than non-tip cells - Yetkin-Arik, B. (Sci Rep, 2019)
Formation of new blood vessels by differentiated endothelial tip cells, stalk cells, and phalanx cells during angiogenesis is an energy-demanding process. How these specialized endothelial cell phenotypes generate their energy, and whether there are differences between these phenotypes, is unknown. This may be key to understand their functions, as (1) metabolic pathways are essentially involved in the regulation of angiogenesis, and (2) a metabolic switch has been associated with angiogenic endothelial cell differentiation. With the use of Seahorse flux analyses, we studied metabolic pathways in tip cell and non-tip cell human umbilical vein endothelial cell populations. Our study shows that both tip cells and non-tip cells use glycolysis as well as mitochondrial respiration for energy production. However, glycolysis is significantly lower in tip cells than in non-tip cells. Additionally, tip cells have a higher capacity to respond to metabolic stress. Finally, in non-tip cells, blocking of mitochondrial respiration inhibits endothelial cell proliferation. In conclusion, our data demonstrate that tip cells are less glycolytic than non-tip cells and that both endothelial cell phenotypes can adapt their metabolism depending on microenvironmental circumstances. Our results suggest that a balanced involvement of metabolic pathways is necessary for both endothelial cell phenotypes for proper functioning during angiogenesis.